The tip of the muscle is a dominant location of ventricular ectopy originating from papillary muscles in the left ventricle - Peichl, Petr; Baran, Jakub; Wichterle, Dan; Čihák, Robert; Skála, Tomáš; Aldhoon, Bashar; Jan, Matevž; Antolič, Bor; Kautzner, Josef (Journal of cardiovascular electrophysiology, 2018)
INTRODUCTION: Frequent ventricular premature complexes (VPCs) may cause symptoms and/or lead to deterioration of LV systolic function. Although frequent VPCs may be abolished by catheter ablation, it may be challenging in case of their origin from the LV papillary muscles (PMs). Our collaborative study aimed to analyze in detail the site of origin and the outcome of ablation. METHODS: Consecutive 34 patients (males: 68%; aged 62 ± 12 years; LV ejection fraction: 50 ± 9%) undergoing catheter ablation of VPCs originating from PMs were included. All procedures were guided by intracardiac echocardiography. RESULTS: The size and shape of PMs were highly variable. The length of anterolateral and posteromedial PM was 23 ± 4 mm and 28 ± 7 mm, respectively. In about one-third of patients, the PM was formed by two distinctly separate heads. The ectopic foci were located on anterolateral, posteromedial or both PM in 35%, 56% and 9% of cases, respectively. Their location was found within the distal, mid, or proximal (basal) third of PM in the 67%, 19%, and 14%, respectively. A total of 86% of PM foci were acutely abolished and long-term success was achieved in 65% of patients. Absence of VPCs of other morphologies and a high burden of ectopic activity before ablation were associated with favorable clinical outcome. CONCLUSION: VPCs originate predominantly from the distal portion of the PM. This knowledge may facilitate the mapping in patients with infrequent ectopic beats. Intracardiac echocardiography is of crucial importance for navigation of the ablation catheter and for assessment of its stability at PM target sites.
Keywords: senioři; elektrofyziologické techniky kardiologické; akční potenciály; Action Potentials; echokardiografie; Europe; Time Factors; katetrizační ablace; ventricular premature complex; Evropa; Echocardiography; Middle Aged; catheter ablation; mužské pohlaví; srdeční komory; papilární svaly; funkce levé komory srdeční; Ventricular Premature Complexes; Heart Rate; Electrophysiologic Techniques, Cardiac; srdeční frekvence; Catheter Ablation; ženské pohlaví; komorové extrasystoly; Humans; Heart Ventricles; časové faktory; cardiomyopathy; lidé středního věku; Papillary Muscles; papillary muscle; Female; Aged; intracardiac echocardiography; lidé; Male; Ventricular Function, Left